The Design And Implementation Of An E-Assessment System For Computer Literacy Skills - Avgousti, Sotiris; Masouras, Panicos (My University, 2010)
The increasing demand for computer literacy skills worldwide led into the development of assessment tools and systems. This paper presents the design and implementation of such a system. It explains the system’s technical architecture and components, its functionalities and services and discusses the pedagogical and educational aspects embedded in the design.
Keywords: Computer literacy